Technology Changing the World: A Journey from the Beginning to the Digital Era Currently - Ratpholthi, Salinrada; Aukaew, Amonwan (Research and Development Journal Sisaket Rajabhat University, 2025)
This research aims to 1) study the development of technology from the Paleolithic period to the present, 2) study the changes of technology in each era, 3) study the current and future situation of technology, and 4) study the importance of technology by collecting data from reliable online sources. The research results found that the development of technology in each era is different. The development of technology is a process that causes changes and developments in many aspects of human life. Starting from the use of basic tools in ancient times, the invention of machinery in the Middle Ages, and the Industrial Revolution in the 18th and 19th centuries, which led to the development of more efficient machinery and transportation. In the 20th and 21st centuries, technology has entered the digital age and developed computers, the Internet, and mobile communications, which have greatly changed the way people communicate and work. There are also advances in medicine and health, including medical imaging technology and biological therapies. In the present and future, the development of technologies is faster and more diverse, such as artificial intelligence (AI), machine learning, and 5G/6G communication networks. The development of these technologies will not only affect our daily lives, but also have the potential to change the global economic and social structure.